Examination of quality of life in patients using exenatide with different dimensions - Siddika Ersoy; Ismail Hakki Ersoy; Sukran Ozkahraman-Koc (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the effects of exenatide treatment on type-2 diabetes mellitus patients’ quality of life. Methods: The cross-sectional study was conducted from March 1 to June 30, 2019, after approval from Suleyman Demirel University, Isparta, Turkey, and comprised type 2 diabetes mellitus patients of either gender under exenatide treatment. Data was collected using a questionnaire during face-to-face interview and included sociodemographic and clinical information along with the World Health Organisation-5 well-being index, the obesity awareness and insight scale, the obesity-specific quality of life scale and the coping orientation to problems experienced-brief inventory. Data was analysed using SPSS 22. Results: Of the 146 patients, 82(56.2%) were female. The overall mean age was 50.6±11.5 years, mean duration of diabetes was 7.4±4.3 years, and mean exenatide use was 9.1±6.6 months. The most common reason cited in favour of exenatide was related to weight-loss 121(82.9%). The patients scored the highest score on the ‘Awareness’ subscale of the obesity awareness scale 29.54±5.42. Conclusion: Exenatide use was effective in improving quality of life, and weight-loss was considered a secondary gain by the diabetics. Key Words: Diabetes mellitus, Exenatide, Quality of life, Patients.